SUBSTITUTION OF PETROLEUM BASE WITH MES BASE SURFACTANT FOR EOR: LABORATORY SCREENING - Sugihardjo Sugihardjo; Hestuti Eni (Testing Center for Oil and Gas LEMIGAS, 2014)
Most of Indonesian oil fi eld had been categorized as mature fi led in which production had been declinedfor some time. Therefore EOR (Enhanced Oil Recovery) technology is a must to be implemented to thesekinds of fi eld. There are several EOR technologies had been employed successfully in laboratory and alsofi eld scales, including gas, thermal, and chemical injection. Most Indonesian oil fi elds have productivelayers depths below 2200ft that will not suitable for gas injection. So that chemical injections become animportant alternative that can be implemented to more wide range of depths. These technologies coveralkaline, surfactant, and polymer injection. This paper will highlight the selection and formulation ofsurfactant formulated from MES (Methyl Ester Sulfonates) produced from Palm Oils. These palm oils areavailable very abundant in Indonesia due to plenty farm palm oil in Indonesia. Normally Surfactants areformulated from petroleum sulfonates which are generated from petroleum base. By Using Surfactant that willbe manufactured from palm oil, it will be expected that the price will be cheaper compare to the surfactantfrom petroleum. A series of researches have been done to select the sources of palm oils, producing MESby sulfonation processes, and fi nally surfactant screening for EOR. Several types of MES produced fromvaries of palm oil taken from market such as: CPO (crude palm oil), several packed palm oils of differenttrademarks have been generated. These MES, then, have been given codes to differentiate among these MESsuch as: 1. CCO-MES (A), 2. CCO ME-MES (B), 3. Oleic Acid- MES (C), 4. Natrium Bisulfi t- MES1 (D),5. ME+H2SO4-MES2 (E), 6. CPO-MES (F). These MES production, then, have been formulated to becomesurfactant formula by adding some chemicals and solvent. After that alkaline ((Na2CO3) with optimizedconcentrations were added to generate the best EOR properties. All those Surfactant-MES have been testedusing Lemigas standard laboratory EOR screening; those are compatibility tests, IFT measurements, thermalstability, adsorption, fi ltration, phase behavior, imbibitions and core fl ooding. The result of the screening ofthe MES-chemicals mixtures shows that mixture of CPO-MES (F) with chemical and solvent with the mixturecomposition denoted as FChS811 has the best performance. 1% of this mixture has the best properties forEOR after adding 0.1% of Alkaline (Na2CO3). Laboratory test results indicates that fulfi ll screening criteriasuh as good compatibility and no precipitation, low IFT, thermal stability, low adsorption, low fi ltrationratio, Winsor type-I phase behavior, high RF on imbibition and core fl ooding tests. This Surfactant-MESmixture has a potential to be implemented for a fi eld trial with Huff and Puff method.